Hubungan Pola Asuh Orang Tua dengan Penyalahgunaan Napza Pada Remaja di Sentra Pangukrangi di Takalar - Nuriftital Jannah; Muh Daud (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research aims to determine the relationship between parental parenting patterns and drug abuse among adolescents at the Sentra Pangukrangi Takalar . The respondents in this study were 75 adolescent who were undergoing rehabilitation. The measuring instruments used are the parenting style scale and the drug abuse scale. Data were analyzed using the Pearson Product Moment correlation technique. The results of the study showed that there was a positive relationship between parenting styles and drug abuse in the Pangukrangi Takalar center, r = 0.263. This illustrates that the higher the implementation of parenting patterns with control, the higher the drug abuse among adolescent. The implication of this research is to reduce the level of drug abuse in Adolescent by providing appropriate parenting patterns.